Sliding Mode Control for Multiagent System with Time-Delay and Uncertainties: An LMI Approach. (11th November 2013) - Guo, Pengfei; Zhang, Jie; Lyu, Ming; Bo, Yuming
Abstract : This paper considers the sliding mode control of multiagent systems (MAS) with time-delay and uncertainties in terms of linear matrix inequality (LMI). By constructing virtual feedback control method, the design of control system is simplified for time-delay independent system without uncertainties. For a class of uncertain systems with single time-delay, the essence of SMC design is analyzed in order to acquire a simple method for designing sliding surface. In terms of multiple timedelay system with uncertainties, a sufficient condition for sliding surface with independent time-delay is acquired, while control law is also designed to ensure the robust stability of closed-loop system. Finally, the effectiveness of conclusion is demonstrated by simulation results.